Key Determinants of Infant Mortality Rate in Asian Countries: A Cross-Sectional Analysis - Priya Kumari; Pushpa Choudhary; Manish Singh (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
Key determinants of Infant Mortality across Asian countries are examined in this study using secondary data from the World Development Indicators. By focusing on variables including access to clean water, female literacy rate, health expenditure, immunisation of children, and per capita GDP, the study employs an OLS regression framework for 41 countries. Regression results reveal that improving water accessibility is the most influential factor, followed by a higher literacy rate among females, where a one-unit increase reduces IMR by 0.31 (p < 0.01), indicating its strong explanatory power Health expenditure and child immunisation coverage demonstrate a negative relation with IMR, with coefficients of −0.84 and −0.21, respectively, although the health spending effects vary across regions. Lastly, higher per capita GDP contributes to reducing the IMR. To ensure the validity and reliability of the data results, diagnostic tests, including Pairwise correlation, Multicollinearity, and Heteroskedasticity, were conducted. These tests confirm the model’s robustness, allowing for accurate interpretation while also taking into account structural heterogeneity and disparities across countries that shape differential health outcomes. Model’s R² (0.81), values indicate strong explanatory power, suggesting that selected variables account for a substantial portion of the IMR variations across Asian countries. The findings offer crucial insights suggesting that interventions, including improving water access, enhancing female literacy, and higher public health expenditure, can contribute to reducing the IMR in regions.